Prarancangan Pabrik Dodekilbenzena dari Dodekena dan Benzena dengan Proses DETAL Kapasitas 60.000 Ton/Tahun - Santoso, Edi, Emi Erawati, S.T,. M.Eng, Eni Budiyati, S.T., M.Eng (2016)
Surfactant is the most important thing in cleanlines, one of the most usable surfactant is sodium dodecylbenzene sulfonat which produced from linear alkyl benzene (LAB). This surfactant is cheaper and easier to sulfonate between the other surfactant. One of the most usable LAB is dodecylbenzene. This company has 60000 tons/year and will be established in Cilacap at 2021 with 156 employees. This factory will convert the dodecene and benzene ot produce dodecylbenzene with DETAL process at 150 oC and silica alumina as catalyst. The raw material are 2.523,41 kg/h benzene and 5.667,18 kg/h dodecene. Benzene and dodecene will be reacted in Fixed Bed Singletube reactor. The main product is 7.575,76 kg/h dodecylbenzene and the side product is 417.79 kg/h didodecylbenzene. This factory is supported by utility plant such as water supplier with 43.427,21 kg/h capacity, steam supplier unit with 7.837,96 kg/h capacity, electricity unit with 327.12 kW capacity, compressed air unit with 150 m3/h capacity and MFO fuel supply facility with 1.634,19 liters/h. This factory is supported by laboratory unit for controlling the quality. The company are classified as Opened Limited Liability Company with 437.783.460.149 rupiahs fixed capital cost and 142.013.215.637 rupiahs working capital cost need. The economical analysis result shows that the profit before tax are 285.287.473.660 rupiahs per year, profit after tax are 213.965.605.245 rupiahs per year, Return on investment (ROI) before tax are 65,20%, ROI after tax are 48,90%, Pay out time (POT) before tax are 1,33 years, POT after tax are 1,70 years, Break even point (BEP) are 43,63% and Shut down point (SDP) are 29,79% with Discounted cash flow (DCF) are 20%, so the company are feasible to establish. Keywords : Dodecylbenzene, fixedbed singletube, DETAL,